The 15-valent pneumococcal conjugate vaccine V114 induces cross-reactive antibodies against pneumococcal serotype 6C - Yaru Shi; Katrina M. Nolan; Robert L. Burton; Tulin Shekar; Rocio D. Murphy; Natalie Banniettis; Luwy Musey; Ulrike K. Buchwald (Taylor & Francis Group, 2023)
Pneumococcal serogroups consist of structurally related serotypes, and serotype-specific antibodies can cross-react against other serotypes within the same serogroup. Cross-reactivity of vaccine-induced serotype 6A antibodies, and, to a lesser extent, serotype 6B antibodies, to serotype 6C has been demonstrated following receipt of the 13-valent pneumococcal conjugate vaccine (PCV13), which contains serotypes 6A and 6B. V114 is a 15-valent PCV containing the 13 PCV13 serotypes plus two additional serotypes, 22F and 33F. This study assessed cross-reactivity to serotype 6C in recipients of V114 and PCV13 as well as specificity of opsonophagocytic activity (OPA) responses in serogroup 6. Following receipt of V114 or PCV13, the observed OPA geometric mean titers to serotypes 6A, 6B, and 6C were comparable across both vaccination groups (post-single dose in adults ≥50 years of age [n = 250] and from pre- to post-dose 4 in pediatric participants 12-15 months of age [n = 150]). Based on OPA inhibition studies, V114 induced cross-reactive antibodies to serotype 6C in adult and pediatric populations that were specific and comparable to those induced by PCV13. Based on experience with PCV13, V114 may also provide comparable protection against pneumococcal disease caused by serotype 6C; however, this will have to be evaluated in real-world studies.